Penilaian faktor predisposisi recurrent aphthous stomatitis dengan menggunakan Kessler psychological distress scale, food recall, dan food frequency questionnaireAssessment of predisposing factors for recurrent aphthous stomatitis using Kessler psychological distress scale, food recall, and food frequency questionnaire - Ayu Galih Permata Dewi; Erna Herawati; Indah Suasani Wahyuni (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2017)
Pendahuluan: Recurrent aphtous stomatitis merupakan kelainan mukosa rongga mulut, dengan ulser berbatas regular secara berulang. Etiologi belum diketahui, tetapi ada beberapa faktor predisposisi yang dapat menginisiasi, antara lain defisiensi stres dan nutrisi. Laporan kasus ini bertujuan membahas penentuan faktor predisposisi recurrent aphtous stomatitis minor terkait defisiensi nutrisi dan stres emosional dengan menggunakan indikator pengukuran stres dan asupan nutrisi. Laporan Kasus: Seorang wanita berusia 23 tahun mengeluhkan sariawan pada bibir, sakit saat makan, dan berulang 2 bulan sekali. Pasien jarang makan sayur dan buah, serta banyak pekerjaan. Secara klinis ulser berdiameter 2mm, ditutupi pseudomembran putih kekuningan, dengan margin reguler pada mukosa labial kanan atas. Pasien didiagnosis recurrent aphtous stomatitis minor dan diterapi dengan gel Triamcinolone acetonide 0,1%. Faktor predisposisi yaitu stress diukur dengan kuisioner Kessler psychological distress scale, dan asupan nutrisi diukur dengan food recall 24 jam dan food frequency questionnaire. Tingkat stres skala 35 dikategorikan stres berat. Berdasarkan Angka Kecukupan Gizi (AKG) pasien mengalami defisiensi nutrisi terutama asam folat dan zat besi. Penyembuhan terjadi lebih lama, sekitar 16 hari, dibandingkan pasien recurrent aphtous stomatitis pada umumnya. Simpulan: Faktor predisposisi recurrent aphthous stomatitis dapat dinilai dengan menggunakan Kessler psychological distress scale, food recall dan food frequency questionnaire.Kata kunci: Recurrent aphtous stomatitis minor, faktor predisposisi, Kessler psychological distress scale, food recall questionnaire, food frequency questionnaire. ABSTRACTIntroduction: Recurrent aphthous stomatitis is a mucosal abnormality of the oral cavity, with regular border ulcers. The aetiology is unknown, but several predisposing factors can initiate, including stress deficiency and nutrition. This case report was aimed to discuss the determination of predisposing factors of minor aphthous stomatitis related to nutritional deficiencies and emotional stress by using indicators of stress measurement and nutritional intake. Case Report: A 23-years-old woman was complaining mouth ulcers, pain while eating, and recurred every two months. The patient was rarely eating vegetables and fruit, and having a lot of working burden. The ulcer was having a diameter of 2mm clinically, covered with a yellowish-white pseudomembrane, with a regular margin on the right upper labial mucosa. The patient was diagnosed with minor aphthous stomatitis and treated with a 0.1% Triamcinolone acetonide gel. Stress predisposing factors were measured by the Kessler psychological distress scale questionnaire, and the nutritional intake was measured by the 24-hours food recall and a food frequency questionnaires. The 35 scale stress level was categorised as severe stress. Based on the Recommended Dietary Allowance (RDA), the patient was having nutritional deficiencies, especially folic acid and iron. Healing process occurred longer, around 16 days, compared to patients recurrent aphthous stomatitis in general. Conclusion: Predisposing factors for recurrent aphthous stomatitis can be assessed using Kessler’s psychological distress scale, food recall and food frequency questionnaire.Keywords: Recurrent aphthous stomatitis minor, Kessler psychological distress scale, food recall questionnaire, food frequency questionnaire.